Educational Leadership Model Towards a Better Education - Mu'in, Abdul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
Schools need a leader who can create better education for learners. The effective leader, who can understand the needs of learners and able to provide a solution, and also produce a better quality of education. In fact, the behavior of leaders relies heavily on his leadership model. Thus, the leadership model will have much effect to the quality of education. Good facilities and qualified teachers will not give anoptimal results without effective leader. Theoretically, many leadership model need to re-discussed so it can be seen the right leadership model for educational leadership. Effective leadership will be required to set up a school system where the applications can be seen from better learning activities and the result is quality learners. This discussion will emphasis on how each model of leadership influence on the quality of education. The results of this research may provide the potential impact on the advancement of education.